Mediterranean stone pine (Pinus pinea L.) genetic variability for growth traits in a Portuguese provenance trial - Carrasquinho I.; Gonçalves E. (Mediterranean stone pine for agroforestry, 2013)
Provenance field trials provide information on adaptability, growth and yield of the species. Results from these studies have great practical use in the improvement of forest stands, as it can assure sources of seed that provide well-adapted, productive trees in reforestation and afforestation. The aim of this study was to evaluate Mediterranean stone pine adaptive variability, using a provenance trial initiated in Portugal in 1992. The seed lots were obtained with the cooperation of Silva Mediterranea network. The provenance trial included twenty-five seed lots, from seven different countries, collected throughout the species’ native range. In February 1993, twenty-five provenances were established at Sines (38o01’N, 8o42’W) and fifteen at Tavira (37o10’ N, 7 o36’ W). Total height and diameter at breast height were used as indicators of provenance variability. Mixed models were applied to data at different ages obtained from those field trials. Results showed that, at least for a significant level of 0.05, provenance genetic variability for height and diameter at btreast height was found.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)